The rise of Firefox in the web browser industry: The role of open source in setting standards. - Oshri, Ilan; de Vries, HenkJ.; de Vries, Huibert (Business History, 2010)
Recent years have witnessed a continuous erosion of the Microsoft Internet Explorer share in the web browser market, mainly induced by the continuous gains of Mozilla Firefox, an open source software product. This tendency would seem to contradict the well-established belief that in a standards battle 'the strong grow stronger while the weak grow weaker'. The objective of this study is to explain the evolution of web browsers through the analysis of the competitive relationship between the main players in this ongoing battle. We examine two standards battles: first, Netscape versus Microsoft, followed by the more recent battle between Microsoft and Mozilla. The analysis contributes to the understanding of standard battles in the context of open source software. It will be argued that some characteristics of Open Source Firefox, such as the semi-open development approach and the involvement of commercial companies, partially explain the rise of this web browser. Lock-in mechanisms, which historically have been reported to be dominant factors in standards battles, seem to have little impact in the context of open source software.